2014
DOI: 10.1542/hpeds.2014-0045
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmissions Among Children With H1N1 Influenza Infection

Abstract: Objectives: To describe readmissions among children hospitalized with H1N1 (influenza subtype, hemagglutinin1, neuraminidase 1) pandemic influenza and secondarily to determine the association of oseltamivir during index hospitalization with readmission. Methods: We reviewed data from 42 freestanding children’s hospitals contributing to the Pediatric Health Information System from May through December 2009 when H1N1 was the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
2
7
2
1
Order By: Relevance
“…A multicenter retrospective study in the United States revealed that pneumonia/bronchitis, acute asthma exacerbation, empyema, acute respiratory failure, and sepsis were the main reasons for repeated admission among inpatients with influenza infections at index admission . The study also found complications of influenza infections during the index admission, non‐use of neuraminidase inhibitors, and underlying complex chronic medical conditions to be risk factors for repeated admission . However, the relationship between pediatric weight status and readmission because of respiratory infections remains unclear.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…A multicenter retrospective study in the United States revealed that pneumonia/bronchitis, acute asthma exacerbation, empyema, acute respiratory failure, and sepsis were the main reasons for repeated admission among inpatients with influenza infections at index admission . The study also found complications of influenza infections during the index admission, non‐use of neuraminidase inhibitors, and underlying complex chronic medical conditions to be risk factors for repeated admission . However, the relationship between pediatric weight status and readmission because of respiratory infections remains unclear.…”
Section: Discussioncontrasting
confidence: 67%
“…23 The study also found complications of influenza infections during the index admission, non-use of neuraminidase inhibitors, and underlying complex chronic medical conditions to be risk factors for repeated admission. 23 national estimates of the effects of obesity on influenza-related respiratory infections among pediatric inpatients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These ICD-9-CM codes have been previously used to identify hospitalized pediatric patients with the presence of tracheostomy 19,21,25 and laboratoryconfirmed influenza with high specificity and positive predictive value. [26][27][28][29] We excluded patients with any of the following characteristics: (1) age 20 years or older to exclude adult patients; (2) transfer from an outside hospital with inpatient status, given interest in initial treatment of influenza and length of stay (LOS); (3) extreme outliers in LOS defined as median plus 3 times the interquartile range (IQR); (4) death during the index hospitalization because the patients could not have a revisit; (5) presence of surgical procedures unrelated to influenza within first 2 days of hospitalization to minimize the possibility of including patients who acquired or manifested with influenza infection during hospitalizations for other reasons; or (6) missing variables in the database. To prevent overrepresentation by patients with multiple eligible encounters, we first assigned a computer-generated random whole number to each admission episode and subsequently selected 1 admission episode for each patient for analysis.…”
Section: Patient Selectionmentioning
confidence: 99%
“…재입원에 대한 관심이 높아 재입원에 대한 광범위한 통계 적 연구 1,3) 및 소아 천식 4) , 인플루엔자 환자에 대한 연구 5) 를 비롯하여 폐렴 환자에 대한 연구 6,7) 등 활발한 접근이 이루어지고 있다.…”
unclassified